2008
DOI: 10.1002/uog.6254
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester screening markers are altered in pregnancies conceived after IVF/ICSI

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
57
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 53 publications
15
57
1
Order By: Relevance
“…The PAPP-A level was also reduced in the previous studies by Gjerris et al (10), Amor et al (11), and Kagan et al (12), which was the largest study to date. The study reported that the PAPP-A levels were reduced 10% in IVF pregnancies.…”
mentioning
confidence: 58%
“…The PAPP-A level was also reduced in the previous studies by Gjerris et al (10), Amor et al (11), and Kagan et al (12), which was the largest study to date. The study reported that the PAPP-A levels were reduced 10% in IVF pregnancies.…”
mentioning
confidence: 58%
“…Therefore, our proposed ultrasound-based method of screening for T21 could be considered as an alternative to CST, either as routine antenatal care or under special circumstances, e.g. in centers without certified biochemical analyzers or in patients after assisted reproductive techniques who demonstrate higher FPRs from CST at a level of 10.7% due to the significantly lower serum levels of PAPP-A [22]. It can also be considered in all women suffering from chronic diseases, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies showed decreased PAPP-A levels in ART pregnancies combined with unaltered levels of fβ-hCG [9,13,14,16,17,20,21] increased fβ-HCG levels [12,22,23,24] or even decreased fβ-hCG levels [15,25]. Two studies reported only an increase in fβ-hCG levels [10,26], and some studies reported no changes in maternal serum values in ART pregnancies [11,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In ART pregnancies maternal serum marker levels change during the first trimester affecting the risk assessment for DS [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Counseling for prenatal screening of women carrying an ART pregnancy is complicated due to contradictory reports in FTS performance in ART pregnancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation